Comparison of the quality of Chinese ginger juice powders prepared by different drying methods. (21st October 2019) - Guo, Fengqian; Yang, Chunyu; Zang, Chen; Shang, Yue; Zhang, Baoxian; Yu, Hailan; Li, Cui; Duan, Shaofeng
Abstract: In this study, ginger juice powders (GJPs) were obtained from ginger juice using vacuum drying, spray drying, vacuum microwave drying (VMD), and freeze‐drying (FD). The physical properties (water content, dissolving time, and color), chemical compositions (total volatiles, gingerols and shogaol, total phenolic content [TPC]), antioxidant activity, and aerobic bacteria content of the GJPs/redissolved ginger juice were determined and the effect of the drying processes on ginger juice was evaluated. The result showed that FD was optimal at retaining the color, gingerols, shogaol, and total volatiles of the ginger juice, while both VMD and FD could retain a high yield of TPC and the antioxidant activity of the ginger juice. It was also found that all the drying methods were effective in reducing the total aerobic bacteria of the ginger juice. This study proved that the four drying methods had very different effects on the quality of the ginger juice, among which FD was optimal for processing ginger juice. Practical applications: In this study, four processing methods of ginger juice were compared by investigating the physical properties (water content, dissolving time, and color), chemical compositions (total volatiles, gingerols and shogaol, total phenolic content), antioxidant activity, and aerobic bacteria content of the different ginger juice powers prepared. The results will provide new reference for processing ginger. Abstract :